Analysis of directional radiation patterns of a system of flat plane sound sources - Zbigniew ENGEL; Lesław STRYCHNIEWICZ (Archives of Acoustics)
This paper presents a method of determining directional radiation patterns of a system of arbitrary flat surface sound sources, source vibration velocities phase shifted by an arbitrary angle. Also the results of verification studies of this method for a system of two circular pistons are presented.